STUDI HIDROGEOLOGI TERHADAP KAPASITAS DEBIT AIR TANAH MENGGUNAKAN METODE PUMPING TEST PADA DAERAH BIROMARU KABUPATEN SIGI - Harly Hamad (Pascasarjana Universitas Tadulako, 2021)
Groundwater is a natural resource that can be renewed naturally, but the time of renewal is very relative. In meeting the needs of groundwater in the community, it is necessary to strive for groundwater produced can be periodically available. The purpose of this study was to aquifer condition and determine the capacity for groundwater discharge in the Biromaru area, precisely in Lolu Village. The data collection method used is the pumping test long-term test method and the analytical method used is the Neuman curve-fitting method and Theis recovery method. Based on the test and aquifer test results of lithological correlation, value of transmissivity 180,001 m2/day, storativity 3,7 x 10-3, specific yield 2,56 x 10-2, hydraulic conductivity 14,572, permeability 16,488. The potential for groundwater discharge in the study area is between 226,067 cm3/day. The maximum available discharge is 146.88 m3/day, while the groundwater discharge that has been exploited from production wells in the research area is ≥363,461.28 m3 which has been used for ±52 weeks so that the pumping discharge does not exceed the potential groundwater discharge.